Effectiveness of web based educational on improving knowledge of acne vulgaris self medication among senior high school students - Lolita Lolita; Ni Putu Isabela Meita Putri (Universitas Ahmad Dahlan, 2017)
The presence of technology can provide real alternatives to build knowledge in delivering health education materials. The aim of this study was to investigate if web-based education methods may rising a student’s knowledge about self medication of acne. This research using an experimental pretest-posttest control group design while the sampling technique using convenience nonprobability sampling. Inclusion criteria for participants were senior high school students aged 13-19 years, active social media users, and willing to fill out the research questionnaire. Participants were allocated to the exclusion criteria as students who perform routine skin care in the acne treatment. Control group consisted of 62 respondents who were given face to face education and treatment group consisted of 62 respondents who were given website-based education. Data analysis were performed with a student t-test to assess the effect of educational intervention on student’s knowledge. The independent t-test showed there was a significant increase of knowledge between the control and the treatment groups (p = 0,000) with 95% confidence level. This study demonstrate that web-based educational intervention had a significant increase on the student’s knowledge about acne vulgaris self medication.